Islamic governance, sharia supervisory board, environmental performance, and Islamic social reporting: Evidence from Indonesia - Akbar Nugroho, Andes; Cinintya Pratama, Bima; Fakhruddin, Iwan; Wibowo, Hardiyanto (IAIN Surakarta, 2022)
Islamic social reporting has been recognised as a major concern in Islamic accounting research in Indonesia. However, research on this issue still remains more paucity of evidence. The purpose of this study was to determine the effect of Islamic governance scores, sharia supervisory board education, cross membership of sharia supervisory boards, and environmental performance on Islamic social reporting. The population used in this study is Sharia Commercial Banks listed on the Financial Services Authoruty (OJK) during 2008-2020. The sampling technique used was purposive to obtain a sample of 150 companies that met the criteria. This study employed multiple regression analysis using the SPSS program to analyze the data. The results of this study showed that Islamic governance score and environmental performance had a positive effect on the disclosure of Islamic social reporting. On the other hand, the result further indicated that the education of the sharia supervisory board and cross-membership of the sharia supervisory board had no effect on the disclosure of the Islamic social reporting disclosure. The results contribute to providing fruitful insights to Islamic banks that Islamic governance score and environmental performance are two crucial factors determining the Islamic social reporting.